Electrophysiological Correlates of Long-Term Soto Zen Meditation. (6th January 2015) - Pasquini, Henrique Adam; Tanaka, Guaraci Ken; Basile, Luis Fernando Hindi; Velasques, Bruna; Lozano, Mirna Delposo; Ribeiro, Pedro
Abstract : This study aimed to verify the electrophysiological correlates of the changes in long-term regular meditators. We use modern techniques of high-resolution electroencephalography applied to slow potentials, power spectra, and potencies related to the events. To obtain encephalographic records, we use an assembly of 128 channels in 31 subjects (17 Soto Zen Buddhist meditators). The motivation of this study was to determine whether the induced beta power would present an increase in meditators as well as a decrease in induced theta/beta ratio in absolute and relative values. However, opposite to what we expected, no significant change was found in the beta frequency. In contrast, the main findings of the study were correlations between the frequency of weekly meditation practice and the increased theta induced relative power, increase of induced power ratio (ratio theta/beta), and increase of the ratio of induced relative powers (theta/beta ratio) during our task that featured an "adapted meditation, " suggesting that the meditative state of "mindfulness" is much more related to the permittivity of "distractions" by the meditators, with a deliberate reduction of attention.